2019
DOI: 10.1017/s1743921319006446
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase reaction kinetics of complex organic molecules at temperatures of the interstellar medium: The OH + CH3OH case

Abstract: Recent experimental and theoretical works concerning gas-phase radical-neutral reactions involving Complex Organic Molecules are reviewed in the context of cold interstellar objects with a special emphasis on the OH + CH3OH reaction and its potential impact on the formation of CH3O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…[96][97][98][99] There have been significant advances in low-temperature studies of reactions involving radicals and oxygenated volatile organic compounds or complex organic molecules. Systems that have received particular attention include reactions such as OH + CH 3 OH, OH + CH 3 CHO, OH + CH 3 C(O)CH 3 , and CH + H 2 CO. [100][101][102][103][104][105][106][107][108][109][110][111] While many of these CRESU studies have focused on the measurement of rate coefficients, in several cases interesting reaction dynamics were also observed. For example, several OH reaction pathways that involved tunnelling through the abstraction activation barrier were found to yield rate coefficients independent of pressure.…”
Section: Flow Tube Methodsmentioning
confidence: 99%
“…[96][97][98][99] There have been significant advances in low-temperature studies of reactions involving radicals and oxygenated volatile organic compounds or complex organic molecules. Systems that have received particular attention include reactions such as OH + CH 3 OH, OH + CH 3 CHO, OH + CH 3 C(O)CH 3 , and CH + H 2 CO. [100][101][102][103][104][105][106][107][108][109][110][111] While many of these CRESU studies have focused on the measurement of rate coefficients, in several cases interesting reaction dynamics were also observed. For example, several OH reaction pathways that involved tunnelling through the abstraction activation barrier were found to yield rate coefficients independent of pressure.…”
Section: Flow Tube Methodsmentioning
confidence: 99%
“…For instance, in the hydrogen abstraction reaction CH 3 OH + OH → [CH 3 OH···OH] → CH 2 OH + H 2 O depicted in Figure , the OH radical forms a pre-reactive complex by hydrogen bonding with the hydroxyl group of the methanol (CH 3 OH) before abstracting a methyl hydrogen via a tunneling mechanism to form products. Because the transition state is chiral but the reactants are not, σ = 2 for this reaction. There is also a secondary reaction, which we do not consider here, in which the hydroxyl hydrogen is abstracted instead.…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature results on OH + CH 3 OH show the results to be independent of total density, hence binary, but there are theoretical (Gao et al, 2018) and experimental results to the contrary. For example, Ocaña et al (2019) showed the process to show some pressure dependence at 120-150 K, whereas no pressure dependence was found at temperatures below 100 K. A number of other theoretical treatments, including the quasiclassical trajectory approach and the ring polymer approach have been discussed by Canosa (2019). From the point of view of astrochemistry, if the OH + CH 3 OH reaction is indeed rapid and binary at 10 K, it is clearly important in the formation of CH 3 O (Acharyya et al, 2015;Balucani et al, 2015).…”
Section: Reactions With a U-shaped Rate Dependence On Temperaturementioning
confidence: 99%